2021
DOI: 10.3389/fnut.2021.670422
|View full text |Cite
|
Sign up to set email alerts
|

Updated Database and Trends of Declared Low- and No-Calorie Sweeteners From Foods and Beverages Marketed in Spain

Abstract: Background: The past few years have witnessed an increase in the availability of food products containing one or more low- and no-calorie sweeteners (LNCS) in the Spanish market, mostly due to the new massive reformulation plan. However, these are not included in food composition tables or databases, and, therefore, assessment of their intake among the population is complex. This study aims to update a database including commercialized foods and beverages.Method: A systematic search of ingredients information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
3
9
0
1
Order By: Relevance
“…We found out that combination of two LNCS is the most common, with acesulfame K and sucralose emerging as the most frequent blend. The same result was also reported in Spain, across the whole food supply (15). Blends can intensify the sweet taste of individual LNCS and prevent an unpleasant aftertaste (50).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We found out that combination of two LNCS is the most common, with acesulfame K and sucralose emerging as the most frequent blend. The same result was also reported in Spain, across the whole food supply (15). Blends can intensify the sweet taste of individual LNCS and prevent an unpleasant aftertaste (50).…”
Section: Discussionsupporting
confidence: 71%
“…Even more frequent use of LNCS in beverages was reported in Spain (39%; 2013) (37), but the latter study was conducted with a very different methodological approach, using food consumption survey data. Very recently, a study with a methodological approach similar to our study was also conducted in Spain (15), but because only foods with LNCS were investigated, the proportion of use of LNCS was not calculated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substitution of sugars with artificial sweeteners is also often used as a strategy for reducing dietary sugar intake. Studies in Europe [66,67] and in Hong Kong [68] have found that the use of low calorie and artificial sweeteners is increasingly more common, whereby manufacturers utilize them to achieve a lower sugar content in their products without affecting taste. The potential health effects of this increased prevalence of low calorie and artificial sweetener use in the population's diet is largely unknown.…”
Section: Discussionmentioning
confidence: 99%